A new drag reducer and a method for preparing the same
Patent Information
- Application Number
- CN202210350382.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-02
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2042-04-02
AI Technical Summary
[0008]本申请提供一种新型减阻剂及其制备方法,能够解决现有减阻剂无法有效分散工艺改进后水泥高触变的问题
[0021]1、本申请的减阻剂同时具备亲水侧链与疏水侧链。减阻剂借助疏水侧链的疏水缔合作用形成立体交联网络结构。立体交联网络结构带有亲水侧链,较单纯梳型结构对水泥的分散性更强,锚固能力更佳,分散能力大幅提高。
Smart Images

Figure BDA0003579794700000011 
Figure BDA0003579794700000021 
Figure BDA0003579794700000071
Abstract
Description
Technical Field
[0001] This application relates to the field of drilling, and more particularly to a novel drag-reducing agent and its preparation method. Background Technology
[0002] The development of drag-reducing agents has gone through three generations. The first generation of drag-reducing agents is represented by lignin, and the second generation is represented by naphthalene-based dispersants. These first two generations of drag-reducing agents mainly adsorb onto the surface of cement particles, using electrostatic repulsion as the dispersion mechanism. The system has a high absolute Zeta potential, therefore its dispersion ability is easily affected by ions, especially high-valence particles. The third generation of drag-reducing agents is polycarboxylate dispersants, mainly based on a stereo (volume) dispersion mechanism. Currently, the research and development of third-generation polycarboxylate dispersants in my country is in full swing, and they have achieved good application results.
[0003] In recent years, environmental pressures have led to restrictions on mining operations, and the wide variety of cement raw material sources has resulted in significant variations in cement composition. This has led to substantial differences between batches of oil well cement, between different packages within the same batch, and even between cements within the same package in extreme cases. Simultaneously, improvements in cement processing have reduced cement fineness and increased thixotropy. These changes in cement composition and increased thixotropy have had a highly detrimental impact on the research and application of admixtures. The industry standard for drag-reducing agents, SY / T5504.3-2018 "Evaluation Methods for Oil Well Cement Admixtures Part 3: Drag Reducing Agents," requires a flowability index n ≥ 0.5 and a consistency coefficient k ≤ 0.7 Pa·sn at 85℃. Rheological tests on a subset of cement batches according to this standard revealed that existing drag-reducing agents largely fail to meet these requirements (as shown in Table 1), even those with good dispersion properties such as comb-type polycarboxylate drag-reducing agents. Ineffective dispersion of cement slurry leads to increased pump pressure and friction during construction, significantly increasing the risk of crushing low-pressure layers and severely impacting construction safety. Therefore, there is an urgent need to develop drag-reducing agents with strong dispersion properties.
[0004] Table 1. Rheological properties of cement slurry with different drag-reducing agents at 85℃
[0005]
[0006]
[0007] Cement grout formula: 792g of Grade G cement + 349g of water + 10.5g of drag reducer. Summary of the Invention
[0008] This application provides a novel drag-reducing agent and its preparation method, which can solve the problem that existing drag-reducing agents cannot effectively disperse the high thixotropy of cement after process improvement.
[0009] The following technical solution was adopted in this application:
[0010] This application provides a novel drag-reducing agent, which is obtained by copolymerization of maleic anhydride, octadecyl methacrylate, 2-acrylamido-2-methylpropanesulfonic acid and allyl polyethylene glycol as monomers, using water as solvent and ammonium persulfate as initiator.
[0011] Furthermore, the amount of maleic anhydride added is 3–15 wt% of the total monomers. The amount of octadecyl methacrylate added is 2–20 wt% of the total monomers. The amount of 2-acrylamido-2-methylpropanesulfonic acid added is 10–60 wt% of the total monomers. The amount of allyl polyethylene glycol added is 30–70 wt% of the total monomers.
[0012] Furthermore, the amount of maleic anhydride added is 5–10 wt% of the total monomers. The amount of octadecyl methacrylate added is 5–10 wt% of the total monomers. The amount of 2-acrylamido-2-methylpropanesulfonic acid added is 30–50 wt% of the total monomers. The amount of allyl polyethylene glycol added is 40–60 wt% of the total monomers.
[0013] Furthermore, the weight-average molecular weight of allyl polyethylene glycol is 2000–3000.
[0014] Furthermore, the amount of ammonium persulfate added is 0.1 to 1 wt% of the total amount of monomers added.
[0015] Furthermore, the amount of ammonium persulfate added is 0.4 to 0.5 wt% of the total amount of monomers added.
[0016] Furthermore, the total monomer concentration is 15–30 wt%.
[0017] This application also provides a method for preparing the above-mentioned drag-reducing agent, comprising the following steps: adding water to a reaction flask, and adding octadecyl methacrylate, maleic anhydride, 2-acrylamido-2-methylpropanesulfonic acid and allyl polyethylene glycol, stirring until completely dissolved, adjusting the pH to 4-9, placing the reaction flask in a constant temperature water bath, and then raising the water bath temperature to 55-85°C, and then adding ammonium persulfate to the reaction flask, reacting for 2-6 hours to obtain the novel drag-reducing agent.
[0018] Further adjust the pH to 6-8.
[0019] Furthermore, sodium hydroxide was used to adjust the pH.
[0020] Compared with the prior art, this application has the following beneficial effects:
[0021] 1. The drag-reducing agent of this application possesses both hydrophilic and hydrophobic side chains. The drag-reducing agent forms a three-dimensional cross-linked network structure through the hydrophobic association of the hydrophobic side chains. This three-dimensional cross-linked network structure, with its hydrophilic side chains, exhibits stronger dispersibility and better anchoring ability for cement compared to a simple comb-like structure, resulting in a significant improvement in dispersion capacity.
[0022] 2. The drag-reducing agent of this application contains a large amount of salt-resistant monomers such as -SO3H. The drag-reducing agent has extremely strong salt resistance and can be applied to brine and seawater slurry preparation systems.
[0023] 3. The drag-reducing agent in this application does not impair strength and has a weak retarding effect.
[0024] 4. The drag-reducing agent of this application has readily available raw materials, low cost, simple synthesis, high yield, safe use, convenient storage, mild application conditions, high monomer conversion rate, and simple product post-processing, making it suitable for industrial production. Detailed Implementation
[0025] The technical methods in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this application without creative effort are within the scope of protection of this application.
[0026] This application provides a novel drag-reducing agent, obtained by free radical polymerization using water as a solvent, ammonium persulfate as an initiator, and maleic anhydride, octadecyl methacrylate, 2-acrylamido-2-methylpropanesulfonic acid, and allyl polyethylene glycol as monomers, under specific temperature and pH conditions. The temperature is 55–85°C, such as 55°C, 70°C, or 85°C. The pH is 4–9, such as 4, 7, or 9. Preferably, the pH is 6–8, such as 6, 7, or 8.
[0027] The amount of maleic anhydride added is 3 to 15 wt% of the total amount of monomers (i.e., the total amount of maleic anhydride, octadecyl methacrylate, 2-acrylamido-2-methylpropanesulfonic acid, and allyl polyethylene glycol). For example, 3 wt%, 10 wt%, and 15 wt%. Preferably, the amount of maleic anhydride added is 5 to 10 wt% of the total amount of monomers, such as 5 wt%, 7 wt%, and 10 wt%.
[0028] The amount of octadecyl methacrylate added is 2-20 wt% of the total monomer content, such as 2 wt%, 10 wt%, or 20 wt%. Preferably, the amount of octadecyl methacrylate added is 5-10 wt% of the total monomer content, such as 5 wt%, 7 wt%, or 10 wt%.
[0029] The amount of 2-acrylamido-2-methylpropanesulfonic acid fed is 10-60 wt% of the total monomer feed, such as 10 wt%, 30 wt%, or 60 wt%. Preferably, the amount of 2-acrylamido-2-methylpropanesulfonic acid fed is 30-50 wt% of the total monomer feed, such as 30 wt%, 40 wt%, or 50 wt%.
[0030] The allyl polyethylene glycol is fed in an amount of 30–70 wt% of the total monomers, such as 30 wt%, 50 wt%, or 70 wt%. Preferably, the allyl polyethylene glycol is fed in an amount of 40–60 wt% of the total monomers, such as 40 wt%, 50 wt%, or 60 wt%. Furthermore, the weight-average molecular weight of the allyl polyethylene glycol is 2000–3000, such as 2000, 2500, or 3000.
[0031] The amount of ammonium persulfate added is 0.1 to 1 wt% of the total monomer content, such as 0.1 wt%, 0.5 wt%, or 1 wt%. Preferably, the amount of ammonium persulfate added is 0.4 to 0.5 wt% of the total monomer content, such as 0.4 wt%, 0.45 wt%, or 0.5 wt%.
[0032] The total monomer concentration (i.e., the total concentration of maleic anhydride, octadecyl methacrylate, 2-acrylamido-2-methylpropanesulfonic acid, and allyl polyethylene glycol) is 15–30 wt%, such as 15 wt%, 25 wt%, and 30 wt%. In other words, the amount of water used is limited to achieve a total monomer concentration of 15–30 wt%. Alternatively, the amount of water can be limited to four times the total monomer input.
[0033] This application also provides a method for preparing the above-mentioned drag-reducing agent, comprising the following steps:
[0034] Add water to the reaction flask, along with octadecyl methacrylate, maleic anhydride, 2-acrylamido-2-methylpropanesulfonic acid, and allyl polyethylene glycol. Stir until completely dissolved, adjust the pH to 4-9 (e.g., 4, 7, 9), place the reaction flask in a 25°C constant temperature water bath, stir for half an hour, then raise the water bath temperature to 55-85°C (e.g., 55°C, 70°C, 85°C), and then add ammonium persulfate to the reaction flask. React for 2-6 hours (e.g., 2 hours, 4 hours, 6 hours) to obtain a transparent viscous solution—a novel drag-reducing agent.
[0035] Preferably, the pH is adjusted to 6-8, such as 6, 7, or 8.
[0036] The pH was adjusted using sodium hydroxide, and after stirring to dissolve, the reaction flask was placed in a constant temperature water bath.
[0037] This application employs free radical polymerization to redesign a comb-type polycarboxylate drag reducer, introducing hydrophobic groups to obtain a novel drag reducer with a comb-shaped molecular structure. The main chain is dominated by -COOH and -SO3H, effectively anchoring to the surface of cement particles. The side chains, composed of hydrophilic polyethylene glycol macromonomers, form a solvation layer on the cement surface, exhibiting significant steric hindrance. This, combined with the electrostatic repulsion between the main chain anions, creates a substantial steric repulsion effect. Furthermore, the added hydrophobic side chains form a weakly cross-linked structure during cement slurry preparation through hydrophobic association. This adds steric support to the hydrophilic side chains in addition to their volumetric dispersion, significantly increasing dispersion capability. Simultaneously, the introduction of salt-resistant monomers such as -SO3H gives the drag reducer strong salt resistance. By controlling the weight-average molecular weight within a suitable range, it can effectively disperse in oil well cement systems and is suitable for freshwater, saltwater, and seawater systems. It exhibits good rheological properties, does not compromise strength, and has a slight retarding effect on setting.
[0038] The following detailed description is provided with reference to specific embodiments:
[0039] In the following examples of this application, maleic anhydride, ammonium persulfate, sodium hydroxide, and sodium chloride were all purchased from Sinopharm Chemical Reagent Company and were of analytical grade; 2-acrylamido-2-methylpropanesulfonic acid and sodium styrenesulfonate were purchased from Shouguang Runde Chemical Co., Ltd. and were of chemical grade. Allyl polyethylene glycol (APEG) was purchased from Jiangsu Haian Petrochemical Plant, with a weight average molecular weight of 2000-3000 (labeled as APEG-weight average molecular weight, such as APEG-2400 indicating allyl polyethylene glycol with a weight average molecular weight of 2400), and was of chemical grade. Octadecyl methacrylate was purchased from Shandong Li'ang New Material Technology Co., Ltd. and was of chemical grade. Grade G high sulfur-resistant cement was purchased from various cement manufacturers and was of commercial grade. The seawater used was from the Bohai Sea.
[0040] Example 1: 400 ml of water was added to a four-necked flask equipped with a stirrer, nitrogen inlet, venting tube, and thermometer. 10 g of octadecyl methacrylate, 3 g of maleic anhydride, 30 g of 2-acrylamido-2-methylpropanesulfonic acid, and 57 g of allyl polyethylene glycol (APEG-2000) were added and stirred at room temperature until completely dissolved. The pH was adjusted to 4, and after stirring to dissolve, the four-necked flask was placed in a constant temperature water bath. The water bath temperature was then raised to 85°C, and 0.8 g of ammonium persulfate solution was added to the mixture, and the reaction was carried out for 3 hours. A novel drag-reducing agent, D1, was obtained.
[0041] Example 2: 400 ml of water was added to a four-necked flask equipped with a stirrer, nitrogen inlet, venting tube, and thermometer. 2 g of octadecyl methacrylate, 15 g of maleic anhydride, 23 g of 2-acrylamido-2-methylpropanesulfonic acid, and 60 g of allyl polyethylene glycol (APEG-2500) were added and stirred at room temperature until completely dissolved. The pH was adjusted to 9, and after stirring to dissolve, the four-necked flask was placed in a constant temperature water bath. The water bath temperature was then raised to 55°C, and 1 g of ammonium persulfate solution was added to the mixture, reacting for 6 hours. A novel drag-reducing agent, D2, was obtained.
[0042] Example 3: 400 ml of water was added to a four-necked flask equipped with a stirrer, nitrogen inlet, venting tube, and thermometer. 20 g of octadecyl methacrylate, 3 g of maleic anhydride, 30 g of 2-acrylamido-2-methylpropanesulfonic acid, and 47 g of allyl polyethylene glycol (APEG-2400) were added. The mixture was stirred at room temperature until completely dissolved. The pH was adjusted to 6. After stirring to dissolve, the four-necked flask was placed in a constant temperature water bath, and the water bath temperature was raised to 65°C. Then, 0.5 g of ammonium persulfate solution was added to the mixture, and the reaction was carried out for 6 hours. A novel drag-reducing agent, D3, was obtained.
[0043] Example 4: 400 ml of water was added to a four-necked flask equipped with a stirrer, nitrogen inlet, venting tube, and thermometer. 10 g of octadecyl methacrylate, 10 g of maleic anhydride, 50 g of 2-acrylamido-2-methylpropanesulfonic acid, and 30 g of allyl polyethylene glycol (APEG-2100) were added. The mixture was stirred at room temperature until completely dissolved. The pH was adjusted to 8. After stirring to dissolve, the four-necked flask was placed in a constant temperature water bath, and the water bath temperature was raised to 70°C. Then, 0.4 g of ammonium persulfate solution was added to the mixture, and the reaction was carried out for 3 hours. A novel drag-reducing agent, D4, was obtained.
[0044] Example 5: 400 ml of water was added to a four-necked flask equipped with a stirrer, nitrogen inlet, venting tube, and thermometer. 5 g of octadecyl methacrylate, 5 g of maleic anhydride, 30 g of 2-acrylamido-2-methylpropanesulfonic acid, and 60 g of allyl polyethylene glycol (APEG-3000) were added and stirred at room temperature until completely dissolved. The pH was adjusted to 8, and after stirring to dissolve, the four-necked flask was placed in a constant temperature water bath. The water bath temperature was then raised to 80°C, and 0.4 g of ammonium persulfate solution was added to the mixture, and the reaction was carried out for 5 hours. A novel drag-reducing agent, D5, was obtained.
[0045] Example 6: 400 ml of water was added to a four-necked flask equipped with a stirrer, nitrogen inlet, venting tube, and thermometer. 8 g of octadecyl methacrylate, 7 g of maleic anhydride, 30 g of 2-acrylamido-2-methylpropanesulfonic acid, and 55 g of allyl polyethylene glycol (APEG-2400) were added. The mixture was stirred at room temperature until completely dissolved. The pH was adjusted to 7. After stirring to dissolve, the four-necked flask was placed in a constant temperature water bath, and the water bath temperature was raised to 65°C. Then, 0.5 g of ammonium persulfate solution was added to the mixture, and the reaction was carried out for 3 hours. A novel drag-reducing agent, D6, was obtained.
[0046] The six samples synthesized in Examples 1 to 6 were subjected to rheological tests in accordance with "SYT 5504.3-2018 Evaluation Method for Oil Well Cement Admixtures Part 3: Drag Reducers". The results are shown in Table 2.
[0047] Table 2. Rheological properties of cement slurry with drag-reducing agent at 85°C
[0048]
[0049] Note: Cement grout formula: 792g Shengwei G-grade cement + 349g grouting water + 11.88g drag-reducing agent. Saturated brine is a 36% sodium chloride aqueous solution by weight.
[0050] As can be seen from the table, the novel drag-reducing agent system exhibits excellent dispersion, with rheological parameters far exceeding the industry standard requirements of n≥0.5 and K≤0.7Pa.sn.
[0051] The rheological properties of drag-reducing agent D6 were evaluated using Grade G cements from Aksu, Kuqa, Shengwei, Harbin, Tongli, and Jidong, and the results are shown in Table 3.
[0052] Table 3. Rheological properties of cement paste systems prepared with different cements using D6 at 85℃
[0053]
[0054] Note: Cement grout formula: 792g G grade cement + 349g water + 11.88g drag reducer D6.
[0055] As can be seen from the table, drag reducer D6 has good adaptability to different types of cement and can be effectively dispersed in all of them.
[0056] The drag reducer D6 was thickened and tested for compressive strength according to "SYT 5504.3-2018 Evaluation Method for Oil Well Cement Admixtures Part 3: Drag Reducers". The formula was: 792g Shengwei G-grade cement + 349g fresh water + 11.88g drag reducer D6. The results are shown in Table 4.
[0057] Table 4. Thickening and compressive strength properties of cement slurry with drag-reducing agents.
[0058]
[0059] Note: Cement grout formula: 792g G grade cement + 349g water + 11.88g drag reducer D6.
[0060] As can be seen from the table, the new drag-reducing agent system does not compromise strength and has a slight delay in setting.
[0061] The foregoing has shown and described the basic principles, main features, and advantages of this application. Those skilled in the art should understand that this application is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of this application. Various changes and modifications can be made without departing from the spirit and scope of this application. The scope of protection claimed by this application is defined by the appended claims, specification, and their equivalents.
[0062] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application and are not intended to limit the scope of protection of this application. Although this application has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of this application without departing from the substance and scope of the technical solutions of this application.
Claims
1. A novel drag-reducing agent, characterized in that, A novel drag-reducing agent was obtained by copolymerization using water as solvent, ammonium persulfate as initiator, and maleic anhydride, octadecyl methacrylate, 2-acrylamido-2-methylpropanesulfonic acid and allyl polyethylene glycol as monomers. The amount of maleic anhydride fed is 3-15 wt% of the total monomer feed. The amount of octadecyl methacrylate added is 2-20 wt% of the total monomer amount; The amount of 2-acrylamido-2-methylpropanesulfonic acid fed into the feed is 10-60 wt% of the total monomer feed. The amount of allyl polyethylene glycol added is 30-70 wt% of the total monomer content; The total concentration of monomers is 15–30 wt%; The amount of ammonium persulfate added is 0.1 to 1 wt% of the total monomer content; The weight-average molecular weight of the allyl polyethylene glycol is 2000-3000.
2. The novel drag-reducing agent as described in claim 1, characterized in that, The amount of maleic anhydride fed is 5-10 wt% of the total monomer feed. The amount of octadecyl methacrylate added is 5-10 wt% of the total monomer content; The amount of 2-acrylamido-2-methylpropanesulfonic acid fed into the feed is 30-50 wt% of the total monomer feed. The amount of allyl polyethylene glycol added is 40-60 wt% of the total monomer content.
3. The novel drag-reducing agent as described in claim 1, characterized in that, The amount of ammonium persulfate fed is 0.4 to 0.5 wt% of the total amount of monomers fed.
4. A method for preparing the novel drag-reducing agent according to any one of claims 1-3, characterized in that, Includes the following steps: Add water to the reaction flask, along with octadecyl methacrylate, maleic anhydride, 2-acrylamido-2-methylpropanesulfonic acid, and allyl polyethylene glycol. Stir until completely dissolved, adjust the pH to 4-9, place the reaction flask in a constant temperature water bath, and then raise the water bath temperature to 55-85°C. Then add ammonium persulfate to the reaction flask and react for 2-6 hours to obtain a novel drag-reducing agent.
5. The preparation method according to claim 4, characterized in that, Adjust the pH to 6-8.
6. The preparation method according to claim 4, characterized in that, Sodium hydroxide was used to adjust the pH.
Citation Information
Patent Citations
Drag reducer, preparation method thereof and application of drag reducer
CN108794696A
Drag reducer, preparation method thereof and application of drag reducer
CN108794697A